The problem of surgical treatment of essential or idiopathic megaesophagus - Carrillo Maurtua, Luis (1956)
This article describes the operations that can be discussed in the surgical treatment of essential or idiopathic megaesophagus exposed. Nerve sections, only splanchnic section is practiced by some with a curative purpose. The anastomosis Gröndahl how the cardioplástías Marwedel's way-Wendell, constantly give perfect or good immediate results. Two of our cases (Case No. 1, 2) we present, are typical examples. The future of surgery with these techniques cardioplasty anastomosis or darkens the output almost constant reflux of gastric juice into the stomach. The consequences of this are dire reflux. The resulting almost obligatory: peptic esophagitis, is a new or more severe as the disease megaesophagus. The vast majority of surgeons, with few exceptions, has abandoned these interventions has been seen when the remote results.